Various Uses of Topological Invariants in Jahangir Graph Jβ, α. (13th September 2022) - Siddique, Imran; Muhiuddin, G.; Mahboob, Abid; Rasheed, Muhammad Waheed
Abstract : Topological indices are analytical indicators of a graph's topology. Graph theory has diverse applications in chemistry and conducts research on molecular structures, and its popularity has steadily increased since then. Many physicochemical attributes of a molecular substance can be identified using topological indices. Topological indices based on these chemical molecular structures can assist researchers in better understanding the physical properties, chemical reactivity, and biological activity. It is a way to fulfill the lack of experiments and give a theoretical basis for the manufacture of many chemical products. The objective of this research is to discuss bidistance degree-based topological invariants in the Jahangir graph.